Effect of the Lateral Exospheric Transport on the Horizontal Hydrogen Distribution Near the Exobase of Mars. Issue 3 (30th March 2018) - Chaufray, J.‐Y.; Yelle, R. V.; Gonzalez‐Galindo, F.; Forget, F.; Lopez‐Valverde, M.; Leblanc, F.; Modolo, R.
Abstract: We simulate the hydrogen density near the exobase of Mars, using the 3‐D Martian Global Circulation Model of Laboratoire de Météorologie Dynamique, coupled to an exospheric ballistic model to compute the downward ballistic flux. The simulated hydrogen distribution near the exobase obtained at two different seasons—Ls = 180° and Ls = 270°—is close to Zero Net Ballistic Flux equilibrium. In other words, the hydrogen density near the exobase adjusts to have a balance between the local upward ballistic and the downward ballistic flux due to a short lateral migration time in the exosphere compared to the vertical diffusion time. This equilibrium leads to a hydrogen density n near the exobase directly controlled by the exospheric temperature T by the relation nT 5/2   =  constant . This relation could be used to extend 1‐D hydrogen exospheric model of Mars used to derive the hydrogen density and escape flux at Mars from Lyman‐ α observations to 3‐D model based on observed or modeled exospheric temperature near the exobase, without increasing the number of free parameters. Key Points: We simulate the hydrogen density near the exobase of Mars We study local time and latitudinal variations of the exospheric hydrogen density at equinox and southern solstice The hydrogen distribution at the exobase of Mars is close to Zero Net Ballistic Flux equilibrium